Dismantling the popular “Gulf Dream’’ stereotype: A reading of Goat Days as a modern slave narrative - Aparna Satheesh Kurup (Navajyoti, International Journal of Multi-Disciplinary Research, 2018)
The initial wave of mass migration of Malayalis, from the Indian state of Kerala, to the Middle Eastern Arab states of the Persian Gulf from 1972 to 1983 is termed as the “Kerala Gulf boom”. Ever since then a myth was in making regarding Kerala’s economy and its key source of income-remittances. Gulf migrants, many of whom were from the working and the lower-middle classes, gradually gained social status which led to the popular belief of the 'Gulf man' being affluent. These gulf dreams have also found its expression in various Malayalam cinema and literature. The objective of this paper is to portray a contrary perspective to this popular belief amidst Keralites on the subject of pravasi (the expatriate) through Najeeb, the protagonist of the novel Goat Days written by Benyamin. The paper aims to explore this alternate world that the protagonist of Benyamin’s book encounters. Based on an oral account of a real survivor, Benyamin challenges these “gulf dreams”. The paper will study the symbolism of the goat, the trials of the exile and his gradual disintegration of selfhood and dreams.